Distribuição generalizada da resistência a fungicidas triazóis e evolução do gene cyp51A em populações de Pyricularia oryzae da brusone do trigo no Brasil - Poloni, Nadia Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The fungus ascomycete Pyricularia oryzae has worldwide distribution as rice pathogen, but it has recently emerged as pathogen causing wheat blast in Brazil. The strobirulin and azole fungicides have been intensively used for management of wheat diseases in the last three decades. The report of resistance of P. oryzae from wheat to strobirulins in Brazil and the inefficiency of azole fungicides indicates a similar scenario. The triazoles represented sterols demethylation inhibitor fungicides group (DMI), characterized by inhibiting the biosynthesis of ergosterol and their target is the 14α-demethylase enzyme, encoded by the cyp51 gene. We determined the azole sensitivity frequency distributions of 180 isolates of P. oryzae of wheat sampled in seven states of the south-central Brazil, based on the EC50 of tebuconazole and epoxiconazole. We described the presence of mutations in the cyp51A gene and built their reticulate phylogeny to identify the evolutionary relationship among haplotypes. We reported that all P. oryzae populations sampled were insensitive to the azoles when compared to the recommended doses for the management of the disease in the field. Based on the sequence of cyp51A gene from P. oryzae of wheat, eight distinct haplotypes were detected. We found seven non-synonymous mutations that could be correlated with resistance to DMI's.

O fungo ascomiceto, Pyricularia oryzae, tem distribuição mundial como patógeno do arroz, mas recentemente emergiu como patógeno causando a brusone do trigo no Brasil. Os grupos de fungicidas estrobirulinas e triazóis tem sido intensivamente utilizados para manejo de doenças do trigo há cerca de três décadas. Há relato de resistência de P. oryzae do trigo a estrobirulinas no Brasil e a ineficácia dos fungicidas triazóis aponta para um cenário semelhante. Os triazóis, inibidores da desmetilação de esteróis (DMI), inibem a biossíntese de ergosterol e possuem como alvo a enzima 14α-demetilase, codificada pelo gene cyp51. Em nosso estudo, determinamos as distribuições de frequência da sensibilidade de 180 isolados de P. oryzae do trigo amostrados de sete estados do Centro-Sul do Brasil, com base na EC50 a tebuconazol e epoxiconazol. Descrevemos, também, a presença de mutações no gene cyp51A e reconstruímos sua filogenia reticulada para esclarecer a relação evolutiva entre haplotipos. Relatamos que todas as populações de P. oryzae amostradas se mostraram insensíveis aos fungicidas testados, comparando-se com as doses recomendadas para o manejo da doença no campo. Com base na sequência do gene cyp51A de P. oryzae do trigo, foram detectados oito haplotipos distintos. Foram encontradas sete mutações não-sinônimas, que podem estar correlacionadas com a resistência à DMI's.
Widespread distribution of triazole fungicide resistance and evolution of the cyp51A gene in populations of wheat blast pathogen Pyricularia oryzae in Brazil
Keywords: Fungus; Sensitivity; Chemical control; Mutations; Fungo; Sensibilidade; Controle químico; Mutações; Cyp51; EC50